DAMPAK PENINGKATAN ASSET, PROFITABILITAS DAN LIKUIDITAS TERHADAP LEVERAGE PERUSAHAAN - Widjaja, Indra (Jurnal Akuntansi, 2014)
Every public company is required to submit financial statements audited bypublic accountant every year. This study examines the effect of the increase in assets, increase in profitability and increase in liquidity on leverage of public companies in the trade, services and investment sector, which are listed on the stock exchanges of Indonesia. This study used multivariate equation model. The study found that the increase in assets providing a positive influence but not significant. The increase in profitability provides positive influence and significant, while the increase in liquidity provides negative effect significantly.